2016
DOI: 10.1016/j.jtho.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Silencing NKD2 by Promoter Region Hypermethylation Promotes Esophageal Cancer Progression by Activating Wnt Signaling

Abstract: NKD2 is frequently methylated in human esophageal cancer, and the expression of NKD2 is regulated by promoter region methylation. NKD2 suppresses esophageal cancer progression by inhibiting Wnt signaling both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…DNA methylation‐based markers have emerged as clinically‐relevant disease markers due to their stability and tissue‐specificity . Previous studies have primarily focused on single candidate and emphasized more on their prognostic role in ESCC . Furthermore, these previous studies have additional shortcomings with respect to sample size analyzed and the inadequate representation of various stages of patients in the discovery and validation steps To overcome these drawbacks, in this current study, we have systematically and comprehensively identified and developed a methylation signature by using stringent criteria during the biomarker discovery phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation‐based markers have emerged as clinically‐relevant disease markers due to their stability and tissue‐specificity . Previous studies have primarily focused on single candidate and emphasized more on their prognostic role in ESCC . Furthermore, these previous studies have additional shortcomings with respect to sample size analyzed and the inadequate representation of various stages of patients in the discovery and validation steps To overcome these drawbacks, in this current study, we have systematically and comprehensively identified and developed a methylation signature by using stringent criteria during the biomarker discovery phase.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Previous studies have primarily focused on single candidate and emphasized more on their prognostic role in ESCC. [30][31][32] Furthermore, these previous studies have additional shortcomings with respect to sample size analyzed and the inadequate representation of various stages of patients in the discovery and validation steps 17,22,23 To overcome these drawbacks, in this current study, we have systematically and comprehensively identified and developed a methylation signature by using stringent criteria during the biomarker discovery phase. Considering the regional "spread" of methylation, we also took into account the methylation status of adjacent probes in a CpG island or DMR while selecting our candidates, thereby reducing the false positive hits and maximizing signal to noise ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot was performed as described previously [5]. Antibodies were diluted according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…While, aberrant epigenetic changes were found frequently in human HCC. DNA methylation was found involved in various cancer-related signaling pathways, including Wnt, p53, and TGF-β signaling [5-9]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, diet can cause profound changes in the epigenome, leading to human disease [9]. Aberrant DNA methylation has been reported in genes involved in cell cycle, DNA damage repair, Wnt, TGF-β, and NF-κB pathways [12,13].…”
Section: Introductionmentioning
confidence: 99%